Pretreatment with Tilianin improves mitochondrial energy metabolism and oxidative stress in rats with myocardial ischemia/reperfusion injury via AMPK/SIRT1/PGC-1 alpha signaling pathway - Li Tian; Wenjiang Cao; Rujing Yue; Yong Yuan; Xinhong Guo; Dongmei Qin; Jianguo Xing; Xinchun Wang (Elsevier, 2019)
Mitochondrial energy metabolism and oxidative stress play a crucial role in ameliorating myocardial ischemia/reperfusion injury (MIRI). Tilianin has been reported to have a significant protection for mitochondrion in MIRI. However, the underlying mechanisms remain unknown. This study investigated whether Tilianin regulates mitochondrial energy metabolism and oxidative stress in MIRI via AMPK/SIRT1/PGC-1 alpha signaling pathway. The MIRI model was established by 30 min of coronary occlusion followed by 2 h of reperfusion in rats. The results revealed that Tilianin significantly reduced myocardial infarction, improved the pathological morphology of myocardium, markedly increased the contents of ATP and NAD+, decreased ADP and AMP contents and the ratio of AMP/ATP, reduced the level of ROS and MDA, enhanced SOD activity, evidently increased the levels of AMPK, SIRT1 and PGC-1 alpha mRNA, up-regulated the expressions of AMPK, pAMPK, SIRT1, PGC-1alpha, NRF1, TFAM and FOXO1 proteins. However, these effects were respectively abolished by Compound C (a specific AMPK inhibitor) and EX-527 (a specific SIRT1 inhibitor). Taken together, this study found that Tilianin could attenuate MIRI by improving mitochondrial energy metabolism and reducing oxidative stress via AMPK/SIRT1/PGC-1 alpha signaling pathway. Keywords: Tilianin, Myocardial ischemia/reperfusion injury, AMPK, SIRT1, PGC-1α